An Integrated Strategy for the Proactive Management of Grapevine Trunk Disease Pathogen Infections in Grapevine Nurseries - Halleen, F.; Fourie, P.H. (South African Journal of Enology and Viticulture, 2016)
The aim of this study was to compare 11 treatment regimes (TR) in grapevine nurseries in order to eradicate trunk pathogens. Grapevine propagation material was subjected to treatments before cold storage, before and after grafting, before planting and after uprooting. Isolations were made from roots, rootstocks and graft unions of uprooted vines. None of the treatments consistently affected the number of certifiable vines produced. TR 1 (benomyl), TR 3 (Sporekill) and TR 4 (Trichoflow) increased root mass. Phaeomoniella chlamydospora was the most frequently isolated pathogen from all plant parts. In general, TR 2, 7, 9 and 11 caused the lowest occurrence of Phaeomoniella. TR 9 consistently reduced the incidence of Phaeoacremonium. Pleurostomophora richardsiae occurred most frequently in graft unions, but treatments were too inconsistent to draw meaningful conclusions. TR 7 (hot water treatment (HWT) of uprooted grapevines) consistently reduced incidences of black foot disease (BFD) pathogens. The highest incidence of Botryosphaeriaceae occurred in graft unions, but all treatments significantly reduced infections. The colonisation of rootstocks and graft unions by Trichoderma was significantly better with TR 4 (Trichoflow). The other Trichoderma treatments (TR 9, 10 and 11) differed from the control treatment only in the graft unions. This is a first report of an integrated strategy covering all the phases of the propagation process, from the moment the nursery receives the propagation material until the dormant vines are removed. TR 9 is recommended for use in nurseries, although HWT of dormant vines is recommended to eradicate BFD pathogens. Benomyl can be replaced by carbendazim when benomyl is no longer available.